Pearson discover history student book 1 (Karachi: Kifayat Publishers, 2024)
Pearson Discover History Book 1 provides a comprehensive introduction to early human history and ancient civilizations. It covers key themes such as the development of early societies, farming and settlements, the rise of cities, and the formation of ancient cultures like Mesopotamia, Egypt, and the Indus Valley. The book presents history through timelines, maps, source-based questions, and engaging visuals that help students understand the sequence of historical events and their significance. Designed for lower secondary learners, the book emphasizes critical thinking, inquiry skills, and the ability to analyze historical evidence. It also encourages learners to ask questions, make comparisons, and explore how the past has shaped the modern world. The content is structured to build foundational historical knowledge in a clear, age-appropriate, and interactive manner.
Pearson Discover History Book 1 is the first in a series designed to introduce young learners to the foundations of history in an engaging and accessible manner. The book focuses on developing historical thinking skills such as chronology, cause and effect, source analysis, and understanding change over time. Through well-structured chapters, colorful illustrations, timelines, and a variety of activities, it encourages students to explore the past and make connections with the present.The content is aligned with international curriculum standards and introduces key historical topics including early human societies, ancient civilizations, and significant cultural and technological developments. The book also promotes inquiry-based learning by incorporating questions, tasks, and project work that stimulate critical thinking and collaborative learning. It serves as an excellent starting point for building historical knowledge and curiosity among lower secondary students.
Keywords: Prehistoric Times; Hunters and Gatherers